DINAMIKA REKRUTMEN MANTAN NARAPIDANA KORUPSI DALAM PROSES PENCALONAN BAKAL CALON LEGISLATIF DI PROVINSI RIAU TAHUN 2019 - Muhammad Hasandi; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Elections are a means of implementing people's sovereignty to elect members of the People's Representative Council (DPR), Regional Representative Council (DPD), and Regional People's Representative Council (DPRD), as well as the President and Vice President. As a reform mandate, the quality of election administration must be improved in order to better ensure healthy competition, dynamic participation, a higher degree of representation and clear mechanisms and accountability. Based on PKPU regulation Number 20 of 2018 concerning the Nomination of Members of the DPR, Provincial and Regency/City DPRD Article 4 paragraph 3 prohibits the nomination of former convicts of drug dealers, sexual crimes against children, and corruption to be accommodated in an integrity pact that must be signed by the leadership of a political party as one of the candidate requirements. However, during the period of nomination for legislative candidates, the Election Supervisory Body identifies prospective legislative candidates with ex-convict backgrounds, especially corruption. As a result, at the Provincial, Regency and City DPRD levels, there are 199 prospective DPRD legislative candidates who are ex-corruption convicts. According to Syamsuddin Haris, the recruitment of legislative members by political parties generally includes three important stages, which include the selection of candidates, screening and selection of candidates who have been recruited, and the determination of candidates and their serial numbers. The party political recruitment mechanism presented by Rush and Althoff is divided into two. First, open recruitment is a system based on open exams. Second, closed recruitment, which is an administrative recruitment system based on patronage. The results of this study are to look at the factors of the names of former legislative candidates convicts of corruption who have the potential to be nominated as legislative candidates or a permanent list of candidates in the 2019 general election. Regency/City against Law Number 7 of 2017 concerning Elections. In its decision, the Supreme Court stated that the prohibition of former convicts in corruption cases from becoming members of the legislature was against the Election Law. The decision resulted in a change in the status of Not Qualifying (TMS) for candidates to be Eligible (MS). Keywords: Recruitment, Dynamics, Nomination